Human Resource Management Policies to Improve Organizational Innovation: A Theoretical Perspective - Iswar Rizal; Derianov Abidin; Muhammad Inshany Renhoran; Hesmi Fahd Roswah; Tias Wahyuni; Huriyana Inas Sumaryan; Freddy Johanis Rumambi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Innovation is crucial for an organization’s competitiveness and sustainability in the global market. This study examines human resource management (HR) policies as key drivers of organizational innovation. HR policies that focus on skill development, diversity, cross-disciplinary collaboration, and experimentation are proven to foster a culture of innovation. Using a qualitative descriptive approach based on literature, this study explores how HR policies enhance individual and team creativity, facilitate new idea exploration, and address innovation challenges through diversity and open communication. The findings suggest that continuous training, respect for diversity, and leadership that encourages risk-taking are critical for innovation success. Companies are encouraged to prioritize policies that promote creative skills, cross-functional teamwork, and diversity integration. Further research is recommended using quantitative methods and case studies to deepen understanding of how these policies impact innovation across different sectors. The results highlight HR’s strategic role in creating a competitive advantage through continuous innovation.